2006
DOI: 10.1111/j.1601-5223.2005.01908.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytological affinities and interfertilities between Lolium temulentum and L. persicum (Poaceae) accessions

Abstract: Interspecific crossing between L. temulentum L. and L. persicum Boiss. & Hohen. ex Boiss. was performed to clarify their interfertility based on the results of chromosome pairing, pollen fertility and seed set. Both parents were normal with a high percentage of chromosome association of ring bivalents in contrast to rod bivalents at metaphase I, pollen fertility and seed set, but F1 hybrids showed different proportions of them for each crossing combination. Chromosome affinity expressed by pairing was certainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The observation of chiasmata was performed in 20 cells per accession and used to obtain the recombination index (RI = [∑ total number of chiasmata ÷ number of cells analyzed] + n value; Darlington 1958). The bivalents were united by one or two chiasmata -the bivalent rods were scored as containing one chiasma while the bivalent rings as having two chiasmata (Senda et al 2005). Then numbers of the post-meiotic products as monads, dyads, triads, tetrads and polyads were registered in order to calculate the meiotic index (%MI = [number of normal tetrads x 100] ÷ number of post-meiotic products counted; Love 1951) and to analyze the variance (Anova).…”
Section: Meiotic and Post-meiotic Behaviormentioning
confidence: 99%
“…The observation of chiasmata was performed in 20 cells per accession and used to obtain the recombination index (RI = [∑ total number of chiasmata ÷ number of cells analyzed] + n value; Darlington 1958). The bivalents were united by one or two chiasmata -the bivalent rods were scored as containing one chiasma while the bivalent rings as having two chiasmata (Senda et al 2005). Then numbers of the post-meiotic products as monads, dyads, triads, tetrads and polyads were registered in order to calculate the meiotic index (%MI = [number of normal tetrads x 100] ÷ number of post-meiotic products counted; Love 1951) and to analyze the variance (Anova).…”
Section: Meiotic and Post-meiotic Behaviormentioning
confidence: 99%
“…temulentum and L. persicum can fertilize each other by artificial crossing and produce fertile hybrid seeds (Senda et al 2005a). We found that the L. persicum-like (i.e., shattering phenotype) accessions were maternally derived from L. temulentum via hybridization with L. persicum, as shown by the results of microsatellite and AFLP analysis (Senda et al 2005b) and cross compatibility studies (Senda et al 2005a). Shattering and non-shattering tendencies of both species are an interesting example of the evolution of weediness.…”
Section: Introductionmentioning
confidence: 65%
“…Though F 1 hybrids showed significantly lower seed set (seed setting %; 49.2% for 01-5-17-2 · 01-5-20-7 and 64.3% for its reciprocal) than parental accessions (90.2% for 01-5-17-2 and 93.9% for 01-5-20-7) (Senda et al 2005a), the amount of sterile seeds did not influence the degree of shattering. All F 1 hybrids of 01-5-17-2 · 01-5-20-7 as well as its reciprocals showed the shattering phenotype (shattering %; 71.4% and 63.8%, respectively), which indicates Table 1.…”
Section: Resultsmentioning
confidence: 95%
“…The mean pollen fertility in our F 1 hybrids under three different conditions was 46.6% (range 42.8-53.1%), and thus was higher than the maximum value (20%) reported by Jenkin (1954a). Senda et al (2005) indicated that an increased chiasma frequency was associated with greater fertility among F 1 hybrids from crosses between L. temulentum and L. persicum accessions. We assume that the pollen fertilities in previous studies were evaluated at temperatures of about 15-20°C, which is optimal for the normal growth of Lolium.…”
Section: Discussionmentioning
confidence: 98%